Saccharomyces boulardii combined with triple therapy alter the microbiota in the eradication of Helicobacter pylori infection - Yan Zhang; Bingyun Lu; Yu Dong; Yifeng Zhang; Qianming Du; Ye Chen; Zhenyu Zhang (Scientific Reports, 2024)
Abstract To assess the effectiveness and safety of combining Saccharomyces boulardii powder with triple therapy as a primary approach for eradicating H. pylori infection, a total of 144 patients who tested positive for H. pylori and diagnosed with non-ulcer dyspepsia underwent endoscopy at two national centers between June 2017 and March 2019 were included. The patients were categorized into three groups using a subsection randomization method and received initial H. pylori eradication treatments. Microbial composition, eradication rates, symptom alleviation, and adverse reactions were monitored on the 14th and 44th days post-treatment. According to PP analysis showed the eradication rates for the SRAC group was 75%, BRAC was 93.18% and RAC was 65.2%. Group BRAC exhibited a marginally higher eradication rate compared to other groups. However, patients receiving Saccharomyces boulardii treatment exhibited an overall reduction in initial dyspepsia symptoms by the end of the treatment period. When employed as a primary strategy, the combination of Saccharomyces boulardii powder with triple therapy displayed notable efficacy and smaller gastrointestinal side effects in eradicating initial H. pylori infections among non-ulcer dyspepsia patients. Moreover, this approach demonstrated advantages in alleviating symptoms, exhibited favorable tolerance, and maintained a high level of clinical safety.